0067 Near-real time monitoring of injury in nebraska by syndromic surveillance. (26th April 2015) - Gonzalez, Sandra; Newmyer, Ashley; Han, Guangming; Qu, Ming; Safranek, Thomas
Abstract : Statement of purpose: Effective injury prevention efforts depend greatly on a surveillance system that monitors event occurrence. Traditionally, the Nebraska Department of Health and Human Services (NDHHS) has defined burden of such events through retrospective analysis of hospital discharge data (HDD). However, these data are limited by timeliness and availability of data elements. An emergency department (ED) based syndromic surveillance (SS) system could be used to enhance injury surveillance by allowing the timely detection of clusters, anomalies and trends. Our objective was to demonstrate the value of ED based SS system data to aid injury surveillance in Nebraska. Methods/Approach: Syndromic Surveillance ED data from pilot Hospital A was analysed for ICD9-CM codes associated with MVC-related injuries (E810-E819), and suicide/self-inflicted injury (E950-E959). For MVC-related injury, time series graphs of weekly ED visits were created for years 2011–2014, and dates corresponding to relevant climate, sports and entertainment events were identified. For suicide/self-inflicted injury, the number of monthly ED visits was determined for years 2011–2014, and the distribution of ED visits was determined by sex, age group, discharge disposition, zip code and injury mechanism. Results: The analysis of the 2011–2014 SS ED data for MVC-related injury indicates a possible temporal trend in the incidence of these injuries in NE. Results suggest that there is an association between weather, sports and entertainment events and spikes in MVC-related injuries. On the other hand, the analysis of the 2011–2014 ED SS data for suicide/self-inflicted injury, indicates a higher percentage of ED visits due to suicide/self-inflicted injury among females than males and among the 15–44 year age group. Most suicide/self-inflicted injury admissions were caused by poisoning. A map of incidence by zip code indicated areas with higher incidence. Conclusions: Results of this pilot study suggests that SS ED data can be used for the timely identification of MVC-related injuries and suicide/self-inflicted injuries. Thus allowing the rapid identification of at risk populations and the timely deployment of prevention measures. Significance and contribution to the field: An ED SS system could be incorporated to support an efficient and rapid prevention response to injuries. Thus allowing the rapid assessment of the burden of these events, and a more timely assessment of prevention efforts.